Virus-Mimetic Fusogenic Exosomes for Direct Delivery of Integral Membrane Proteins to Target Cell Membranes - Yang, Yoosoo; Hong, Yeonsun; Nam, Gi-Hoon; Chung, Jin Hwa; Koh, Eunee; Kim, In-San (WILEY-V C H VERLAG GMBH, 2017)
An efficient system for direct delivery of integral membrane proteins is successfully developed using a new biocompatible exosome-based platform. Fusogenic exosomes harboring viral fusogen, vascular stomatitis virus (VSV)-G protein, can fuse with and modify plasma membranes in a process called "membrane editing." This can facilitate the transfer of biologically active membrane proteins into the target cell membranes both in vitro and in vivo.
Keywords: EXTRACELLULAR VESICLES; FUSION ACTIVITY; CANCER-CELLS; MUSCLE PH; EXERCISE; PEPTIDE; DISEASE